Relationship between Organizational Learning and Performance of Insurance Firms in Kenya (International Journal of Scientific Research and Management (IJSRM), 2017)
The objective of the study was to establish the relationship between organizational learning and firm performance. The study used cross sectional descriptive research design. A descriptive cross-sectional design facilitated determination of relationship between organizational learning, and performance of firms in the insurance industry in Kenya. The population of interest in this study consisted of all the 45 insurance firms offering insurance cover in Kenya. This was a census study since the population was small. Both primary and secondary data were collected and used in the study. The data analysis was done using quantitative techniques. The data collected was first summarized, categorized and coded. Descriptive statistics were used. They consisted of frequency distributions, measures of central tendency (arithmetic mean, median, and mode). Regression models were used to test the hypotheses. The results showed that organizational learning has a positive and statistically significant effect on firm performance in the case of return on assets, growth of market share and the overall firm performance. The study revealed that organizational learning has a significant influence on firm performance both when using return on assets and growth of market share as the dependent variable. Managers in the insurance industry can apply the findings of this study to develop internal capacity to work towards superior performance. Firms must embrace organizational learning as a key resources and this study can be used to demonstrate that it would be worth spending resources to engage in organizational learning.